PENGARUH PENGEMBANGAN KARIER DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA GURU SDN DI KECAMATAN SUHAID - Desi Indriayani; Wahyudi Wahyudi; M. Syukri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study aims to determine the effect of career development and work discipline on the work productivity of elementary school teachers in Suhaid District, Kapuas Hulu Regency. This study uses a quantitative approach, with the type of correlation research. The subjects of the research are elementary school teachers who are civil servants/non civil servants with a minimum working period of two years. This study uses a questionnaire as a data collection technique with data analysis using the IBM SPSS Statisticts 26. From the results of the research, the conclusions are: (1) career development has a strong and positive effect on teacher work productivity; (2) work discipline has a strong and positive effect on the work productivity of elementary school teachers; (3) career development and work discipline simultaneously have a strong and positive effect on the work productivity of elementary school teachers; (4) career development has an influence on the work productivity of elementary school teachers by 34.4%; (5) work discipline has an influence on the work productivity of elementary school teachers by 25.2%; (6) career development and work discipline simultaneously have an effect on the work productivity of elementary school teachers by 38.7%.